2002
DOI: 10.1104/pp.010928
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Phospholipase D Family. Characterization of a Calcium-Independent and Phosphatidylcholine-Selective PLDζ1 with Distinct Regulatory Domains

Abstract: Four types of phospholipase D (PLD), PLD␣, ␤, ␥, and ␦, have been characterized in Arabidopsis, and they display different requirements for Ca 2ϩ , phosphatidylinositol 4,5-bisphosphate (PIP 2), substrate vesicle composition, and/or free fatty acids. However, all previously cloned plant PLDs contain a Ca 2ϩ-dependent phospholipid-binding C2 domain and require Ca 2ϩ for activity. This study documents a new type of PLD, PLD1, which is distinctively different from previously characterized PLDs. It contains at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
298
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(322 citation statements)
references
References 77 publications
12
298
1
1
Order By: Relevance
“…A connection between choline content and root hair elongation was also suggested following the mutation of PLDz1, an enzyme responsible for the degradation of PtdCho into PA and choline (Qin and Wang, 2002;Ohashi et al, 2003). However, the double KO pldz1 pldz2 contradicted these results since it did not exhibit any root hair alteration (Li et al, 2006).…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…A connection between choline content and root hair elongation was also suggested following the mutation of PLDz1, an enzyme responsible for the degradation of PtdCho into PA and choline (Qin and Wang, 2002;Ohashi et al, 2003). However, the double KO pldz1 pldz2 contradicted these results since it did not exhibit any root hair alteration (Li et al, 2006).…”
Section: Discussioncontrasting
confidence: 41%
“…To verify if altered levels of PCho and PEth could lead to the transcriptomic activation or inhibition of specific lipid metabolism pathways, we selected several genes representative of membrane lipid recycling pathways triggered during Pi starvation (Nakamura, 2013). These genes included NPC4 (representative of the nonspecific PLC pathway; Nakamura et al, 2005), PLDz1 and 2, PAH1 and 2 (for the PLD/PAP pathway; Qin and Wang, 2002;Li et al, 2006;Nakamura et al, 2009;Eastmond et al, 2010), and GDPD1, 2, 3, 5, and 6 (for the LAH/GDPD pathway; Cheng et al, 2011). In response to a lack of Pi, we observed that NPC4, PLDz2, and GDPD1, 2, 3, 5, and 6 were induced in wild-type plants as previously reported (Supplemental Fig.…”
Section: Triple Ko Mutant Does Not Mimic or Amplify Phenotypes Causedmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared them to the radioactive molecular species of PtdIns, PtdEtn and PtdCho after a 24 h 33 Pi labeling that reflect the molecular species distribution of the bulk lipids (not shown). The molecular species of radioactive PtdOH after a 10 min cold stress were typical of phosphoinositides, confirming that this radioactive PtdOH resulted almost exclusively from a DAGK activity coupled with phosphoinositide-dependent phospholipase C (PI-PLC) activity as PtdIns is not a substrate of Arabidopsis PLD [22].…”
Section: A Differential Labeling To Detect Ptdoh Proceeding Frommentioning
confidence: 83%
“…According to the sequence characteristics, the PLD gene family can be generally classified into six or seven types, including PLD, PLD, PLD, PLD, PLD, PLD and/or PLD (Elias et al, 2002;Li et al, 2007). The diverse PLD types differentiated depending on their requirements and affinities for Ca 2+ , phosphatidylinositol 4,5-bisphosphate (PIP 2 ) and free fatty acids (Qin and Wang, 2002;Qin et al, 1997). The exception was PLD, which was poorly characterized as of yet (Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%